Stellenwert der Gentherapie in Unfallchirurgie und Orthopädie - Oberholzer, A. (Unfallchirurg, 2006)
Modern molecular and genetic technologies enable the modification of a cellular genome through transfer of specific genes. The various procedures alter specific cell functions, which allow the transfected cell to produce any encoded transgene information. The transfected cell then synthesizes proteins that are normally not produced or only in very small amounts. Numerous animal studies have demonstrated that gene therapy may support and accelerate the healing and regeneration of specific tissues such as skin, tendons, cartilage, and bones. Currently, further animal studies are evaluating new vectors with reduced immunogenicity in the continuous effort to improve the efficacy and safety of gene transfer. In the forthcoming decade we expect gene therapy to have an important influence on the treatment of fractures, cartilage lesions, and infection.